Effects of high frequency vibratory finishing of aerospace components - Wong, Ben Jin (2020)
Vibratory finishing is extensively utilized for surface engineering applications particularly in the aerospace industry. Commercial vibratory finishing operations occur at a frequency range of 15 Hz to 50 Hz. An experimental investigation on the effects of high frequency on surface roughness and process cycle time is reported with the objective of providing a deeper insight into high frequency vibropolishing. The study was orchestrated with the aid of a modified commercial vibratory finishing bowl delivering frequencies up to 75 Hz. Flat Ti-6Al-4V test pieces were subjected to vibropolishing at conventional bowl frequency of 50 Hz and high frequency of 75 Hz to demonstrate the effects of increasing frequency in vibratory finishing. Investigations showed up to 80 percent cycle time reduction when operating frequency was increased to 75 Hz. Statistical tests and force sensors were incorporated to provide an in-depth analysis of the experimental results. Consequently, it was concluded that while high frequency of vibrations had a positive impact on the process cycle time, the orientation of a work piece had negligible influence.